First record of Sphaeronycteris toxophyllum on Bonaire Island - Simal, Fernando; Nassar, Jafet M. (Therya Notes, 2025)
Bats have great dispersal capacities and many species are capable of flying across areas of open sea while migrating, commuting, or foraging, covering a broad range of distances. Our goal was to report and provide possible explanations for the presence of a visored bat, Sphaeronycteris toxophyllum, captured on Bonaire Island, Dutch Caribbean. In October 2023, the bat was found hanging at the stairs of a resort on the west coast of Bonaire, pictures were taken and, immediately after, the animal was captured and transported to the Bonaire Wild Bird Rehabilitation Center. Taxonomic identification was conducted and the bat was properly maintained with food, hydration, and roost until its death. Then, the animal was preserved in ethanol. This is the first known record of S. toxophyllum for Bonaire and the ABC Islands. The specimen corresponds to a female, adult, non-pregnant, no lactating, 19 g weight, forearm length 40.3 mm. Stomach and intestines were examined and found empty, suggesting that the animal did not ingest food during the last hours or days before its death. We propose two possible explanations for the arrival of this bat in Bonaire, the animal either flew from Venezuela’s coast after getting disoriented, crossing nearly 90 km, or it was transported on a boat, used as a temporal roost, that had this island as destination. This finding illustrates the rare, but still possible, events of bat arrivals from the coasts of Venezuela into the ABCs and nearby islands.